The effect of 12 weeks of aerobic training and food restriction on dopaminergic and catalepsy neurons in the brain tissue of Parkinson\'s disease model of rats - Sima Movahed; Jabbar Bashiri; Hasan Pourrazi; Roghayeh Pozesh Jadidi (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Parkinson's disease is a prevalent neurodegenerative disorder characterized by the degeneration of dopaminergic neurons and the presence of catalepsy. This study aimed to investigate the effects of 12 weeks of aerobic training and food restriction on dopaminergic and catalepsy neurons in the brain tissue of Parkinson's disease model of rats. Methods: In this experimental study, 40 male Wistar rats aged 2-3 months were randomly divided into five groups (n=8): healthy control (C), Parkinson's disease model (P), Parkinson's disease model + aerobic training (P+T), Parkinson's disease model + food restriction (P+FR), and Parkinson's disease model + aerobic training + food restriction (P+T+FR). The aerobic training regimen consisted of three months with five sessions per week at an intensity of 75-80% of maximum oxygen consumption. The food restriction group received approximately 11 grams of food daily. Catalepsy was assessed using the rod test, while dopaminergic neurons were quantified through brain sectioning and microscopic counting. Results: The P+T+FR group exhibited a significant increase in dopaminergic neuron count compared to the C, P, P+T, and P+FR groups (P=0.001). Furthermore, a significant reduction in catalepsy was observed in the P+T+RF group compared to the P group (P=0.001). Conclusion: The combination of three months of aerobic training and food restriction resulted in improvements in dopaminergic neuron count and reduced catalepsy in a rat model of Parkinson's disease. These findings suggest that aerobic training and food restriction could serve as potential complementary interventions for Parkinson's disease treatment, alongside pharmacological approaches, warranting further investigation in this area.